Morfologi Tipe Thalus Lichen Sebagai Bioindikator Pencemaran Udara di Taman Bundaran Cibiru Desa Cipadung Kecamatan Cibiru Kota Bandung - Rohim Rohim; Mohammad Haris Musthofa; Irpan Noerdin; Ateng Supriatna (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
This research aims to determine the morphology of thallus lichen types as a bioindicator of air pollution in Cibiru. The method used is exploratory descriptive with survey techniques. Sampling was carried out at the Cibiru roundabout park which has a range of air temperatures and humidity levels, namely an air temperature of 28° and an air humidity level of 77.2%. The results of this research were that 1 type of lichen was found which belongs to the genus Dirinaria, namely Dirinaria applanata, with the characteristic of having irregular and folded lobes with relatively loose ends attached to the substrate, often containing rizines to help them attach to the substrate. The general morphology of the thalus found at the observation site tends to be round, elongated vertically, and irregular. The general morphological color of the thalus found is gray, bluish or almost white. Lichen can be used as a bioindicator for air quality tests, indicating air pollution. With the level of lichen diversity decreasing, the air quality is low.